Radiographic Visualization of Lymphatic System Tips Using Iodochlorol - Quevedo Coloma, Ernesto A. (1965)
The application of the method to the study of radiographic vascular systems , by introducing radiopaque contrast substances within its light, has allowed a better understanding of anatomy , physiology, pathology and treatment. This at first was only targeting the venous and arterial systems ( 9) , in which surgical techniques boom reached through this process , aside perhaps lymphatic system due to technical difficulties for study. However, several attempts to try to visualize it, were made by subcutaneous or intraperitoneal introduction of contrast medium unsuccessfully temporarily abandoning this study. The first successes were obtained by Funaoka in 1930 who injected mercury and iodine salts within the lymphatic system ; was followed : Carvalho et al (1931 , 1934) , Toreff and Stoppani (1932 ) , Monville and Ané (1932 ) , Monke (1932 ) , Zolothrekin (1934 ) , Bennett and Shivas (1954 ), who used different contrast media ( 39 ) . Was Kinmonth and colleagues ( 1952 ) , who corresponded to him to initiate a truly valuable method lymphangiography (23 ) (24 ) , the study of the lymphatic system of man, and whose technique with slight variations is used to present as a guideline for several investigators , thus allowing one standardization study methods.